REPRESENTASI LAKI-LAKI FEMINIS DALAM VARIETY SHOW KOREA THE RETURN OF SUPERMAN (STUDI SEMIOTIKA JOHN FISKE) - Pradnyani Kawiswari, I Dewa Agung Ayu; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT Variety show as one of the television programs consists of signs and meanings. Korean variety show The Return of Superman exhibits the feminist side of a husband who helps his wife in caring for their children and taking care of household chores. Signs representing feminist side of the men on this variety show was analyzed using John Fiske’s semiotics. The results of this research showed that the Korean Variety Show The Return of Superman represents feminist side of men who are caring, tolerant, cultured, liberates in interpersonal partnership. These men use positive polite language, understand the domestic work distribution, and are transparant. This leads to the development of patriarchal ideology in Korea based on the emergence of a new men characteristic. Keywords: Feminist Men, Korean Variety Show, Representation, Semiotics